The Effect of Grammar Translation Method Towards Students’ Writing Ability - Mita Nur Widiyanti Mita (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2023)
English is becoming a subject that focuses on helping students grow their abilities in every aspect. Students are expected to be able to greatly improve their abilities, specifically in the area of writing. Therefore, the researcher uses the Grammar Translation Method to support students in improving their writing skills at school. This study aims to determine the effect of the Grammar Translation Method on students' writing skills, and to know students’ responses towards the Grammar Translation Method. Participants in this study were X gradestudents majoring in BR from SMKN 1 Subang that were selected in the initial population using the convenience sampling method. This is quasi-experimental research with two groups pre-test and post-test design. The instruments in this research were tests and questionnaires. The assumption test includes a normality test using SPSS version 26.0. Data analysis was performed by independent sample t-test and calculate the percentage of the questionnaire data. The results of an independent test got a sig. (2-tailed) of 0.027 < 0.05 means that H0 is rejected and Ha is accepted. And the percentage of the questionnaire shows a good response from the students towards using the grammar translation method. It can be concluded that the grammar translation method has effect on students' writing ability. The findings of this study are expected to serve as a reference for teachers to continue using the Grammar Translation Method in writing lessons, as well as to increase students' desire to learn English further.